Electronic commerce - Schneider, Gary P., 1952- (Boston, Mass. : Thomson Course Technology, 2007)
This is a complete introduction to the world of electronic commerce, including balanced coverage of technical and business topics
Includes bibliographical references and index
Keywords: Electronic commerce; Electronic data interchange; Business enterprises -- Computer networks; Internet marketing